2009
DOI: 10.1180/minmag.2009.073.6.1009
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic and post-magmatic Y-REE-Th phosphate, silicate and Nb-Ta-Y-REE oxide minerals in A-type metagranite: an example from the Turčok massif, the Western Carpathians, Slovakia

Abstract: An electron microprobe study of Y-REE-Th phosphate, silicate and Nb-Ta-Y-REE accessory-mineral assemblages revealed the compositional variations and evolution in post-orogenic, hypersolvus Permian A-type metagranite from Turčok, in the Gemeric Unit, of the Western Carpathians, eastern Slovakia. Prismatic zircon I and allanite-(Ce) are primary magmatic phases. However, the late-magmatic to early-subsolidus processes led to the formation of a more complex younger assemblage: bipyramidal zircon II, xenotime-(Y), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…As examples, Uher et al (2009) found columbite-(Fe) forming rare irregular intergrowths with Nb-Ta-rich rutile in the Prašivá granitic pegmatites, Slovakia. Doroshkevich et al (2009Doroshkevich et al ( , p.1113 described columbite + quartz replacing pyrochlore in the Amba Dongar carbonatite complex, Gujarat, India, and Lahti (2000, p. 112) recorded pyrochlore-microlite replacing marginal parts of columbite crystals and small columbite-group phases occurring in pyrochlore samples from granitic pegmatites of the Eräjärvi district, South Finland.…”
Section: Relationships Between Cgm Composition and Nature Of Accessoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…As examples, Uher et al (2009) found columbite-(Fe) forming rare irregular intergrowths with Nb-Ta-rich rutile in the Prašivá granitic pegmatites, Slovakia. Doroshkevich et al (2009Doroshkevich et al ( , p.1113 described columbite + quartz replacing pyrochlore in the Amba Dongar carbonatite complex, Gujarat, India, and Lahti (2000, p. 112) recorded pyrochlore-microlite replacing marginal parts of columbite crystals and small columbite-group phases occurring in pyrochlore samples from granitic pegmatites of the Eräjärvi district, South Finland.…”
Section: Relationships Between Cgm Composition and Nature Of Accessoriesmentioning
confidence: 99%
“…The abundances of certain non-formula elements are high: P 2 O 5 ≤ 8.24 wt.%, CaO ≤3.02 wt.%; ΣREE 2 O 3 ≤22.44 wt.%; FeO* 4.05 wt.%, and TiO 2 ≤2.05 wt.%, the REE being dominated by the LREE. These elements are known to be incorporated into ThSiO 4 during interaction with hydrothermal fluids (Lumpkin and Chakoumakos 1988;Pointer et al 1988;Johan and Johan 2005;Förster 2006;Berger et al 2008;Uher et al 2009;Soman et al 2010;Piilonen et al 2013). The proportion of OH in the formulae was calculated from charge balance and ranged from 0.0 to 2.4 (Supplementary Table 2b).…”
Section: Thsiomentioning
confidence: 99%
“…The local presence of ilmenite may point to lower f O 2 condition there, consistent with the relatively high Mn content (≤4.65 wt.% MnO) (Cassidy et al 1988). (iii) The increasingly large positive Ce anomalies found in the phases during successive alteration stages may be taken to be a result of oxidising conditions affecting the valency of Ce (Gieré and Sorensen 2004;Pettke et al 2005;Mayer et al 2014;Berger et al 2008;Uher et al 2009). However, the anomalies may equally be related to preferential partitioning of Ce into the fluids.…”
Section: Nature Of Hydrothermal Fluidsmentioning
confidence: 99%
“…The source of fluorine is still unknown, but the circulation of F-rich fluids was noted in supra-subduction zones, due to phengite and /or F-amphibole breakdown (Sheng et al 2013). The high activity of fluorine and phosphorus was noted during hydrothermal alterations elsewhere in the crystalline cores of the Central Western Carpathians (Burda & Dzierżanowski 2005;Szopa 2009;Uher et al 2009;Gawęda & Włodyka 2012;Ondrejka et al 2012).…”
Section: Origin Of the Parent Melt/fluid To The Fluorapatite-rich Veinmentioning
confidence: 99%